Reduced‐order dynamic model for droop‐controlled inverter/converter‐based low‐voltage hybrid AC/DC microgrids – part 1: AC sub‐microgrid. Issue 4 (15th October 2018) - Rasoolzadeh, Arsalan; Salmasi, Farzad Rajaei
Abstract : This study focuses on reduced‐order dynamical modelling of droop‐controlled inverter‐based low‐voltage AC sub‐microgrid in a hybrid AC/DC microgrid. The authors aim to develop a comprehensive reduced‐order model for the low‐voltage AC side in this part. The reduced‐order models are preferred in real‐time calculations. In hybrid microgrids, electrical power is exchanged between the AC and DC sub‐microgrids by a bidirectional AC/DC converter. The distributed energy resources are connected to the main AC bus through power inverters. Voltage and frequency commands are generated by droop controllers for each inverter. For the main AC bus, equations describing voltage magnitude and frequency are derived. Steady‐state values of the phase angles and injected power of the inverters are calculated. The overall non‐linear dynamical and algebraic equations are derived for the low‐voltage AC side, and then linearised around the operating point. To validate the developed model, a hybrid microgrid is implemented in PSCAD. Then, the proposed model for the case study is implemented in Matlab/Simulink and the results are compared with PSCAD outputs. The comparative results show the validity of the developed comprehensive reduced‐order model which can be used in fault detection approaches.